The influence of landscape variation on landform categorization - Williams, Maia (2019)
This paper compares the landform vocabularies of residents from two regions in Portugal. Participants described both their own and the other, less familiar landscapes in response to video footage of the regions. The results indicate that participants used more detailed vocabularies to describe the known landscape compared to the less familiar study site, with detail triggered by individual place recognition. A relationship between landform lexica content and landscape type was observed in the relative placement of detail within each vocabulary. The observed drivers of categorization were the salient features of the landscape (elevation and land cover) and utilitarian motivations (land use, context, and familiarity). The results offer support to the notion of non-universality in geographic object categorization.